Synthetic method of bionic urethral stent and product thereof
By using materials such as PVA, borax and CMCS to form multi-layer hydrogel urethral stents, the shortcomings of existing materials in terms of mechanical properties, biocompatibility and repair effects are solved, and the biocompatibility, self-healing ability and antibacterial effect of urethral stents are achieved, which significantly improves the effect of urethral repair.
Patent Information
- Application Number
- CN202411671206.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-21
AI Technical Summary
The existing tissue-engineering urethral stent materials have shortcomings in terms of mechanical properties, biocompatibility, susceptibility and repair effects, and it is difficult to meet the needs of urethral repair.
Materials such as PVA, borax and CMCS are used to form a multi-layer hydrogel urethral scaffold through freeze-thaw cycle, combining hydrogen bonds and physical tangles to adjust its mechanical strength and biocompatibility, and freeze and melt treatment during the molding of each layer of hydrogel to enhance its self-healing ability and antibacterial effect.
The biocompatibility, non-toxicity, degradability and adjustable mechanical strength of the urethral stent are achieved, with self-healing characteristics and good antibacterial effects, which significantly improves the effect of urethral repair.
Smart Images

Figure CN119656396A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogel urethra stents, and relates to a synthesis method of a bionic urethra stent and a product thereof. Background Art
[0002] Urethral stricture and hypospadias are common diseases in urology, which seriously affect the quality of life of patients, and urethral repair and reconstruction surgery is the primary treatment for patients. Currently, the main grafts used for urethral repair and reconstruction in clinical practice are the patient's own tissues, such as penile skin flaps, oral mucosa, bladder mucosa, and colon mucosa. However, the amount of autologous tissue is limited, and the practice of repairing trauma with healthy tissue will bring many complications to the sampling site.
[0003] Tissue engineering urethra effectively overcomes the above shortcomings, has broad application prospects, and has become a research hotspot in recent years. At present, the types of materials used in urethral tissue engineering can be roughly divided into decellularized matrix, natural source scaffold and synthetic polymer scaffold. Among them, the decellularized matrix retains the original urethral microenvironment, which is more conducive to cell proliferation and tissue regeneration, but insufficient decellularization causes inflammatory response, and excessive decellularization will inactivate growth factors and proteins in the matrix. At present, the ideal decellularization technology is still being explored. Natural source scaffolds have good biocompatibility and are more conducive to cell proliferation and differentiation, but they often degrade quickly and have insufficient mechanical strength. Synthetic polymer scaffolds are widely used, easy to regulate mechanical strength and intrinsic structure, stable physical and chemical properties, and no risk of disease transmission, but their biocompatibility needs to be further improved. Since the 1990s, hydrogels have been the subject of in-depth research by many scientists. As a three-dimensional polymer network, hydrogel has been used in the field of tissue engineering because it has variable geometry, adjustable strength and porous structure, which is very similar to natural ECM, so it may become the best choice for tissue engineering urethral scaffolds.
[0004] Since the urethra is a vascularized hollow elastic organ, it is mainly composed of a thin mucosal layer, a basal layer, and a thicker connective tissue layer. The mucosal layer is mainly composed of urethral epithelial cells, which act as a urine barrier, while the basal layer and connective tissue layer contain muscle cells, fibroblasts, and abundant blood vessels, providing mechanical strength and rich nutrition for the urethra. From the perspective of bionics, developing urethral stent grafts that can simulate the structure and function of the natural urethra may be the best solution for tissue engineering urethra, but most of the existing studies are single-layer or double-layer structures, which cannot achieve the repair effect of the native urethra. In addition, the composition of existing tissue engineering scaffold materials varies, and the mechanical properties are also very different. It is unknown what mechanical properties the scaffold that is most conducive to urethral repair needs to have. Summary of the invention
[0005] The purpose of the present invention is to provide a urethra repair material that is highly similar to the native urethra, has good biocompatibility, is non-toxic, has good degradability, has adjustable mechanical strength, and also has self-healing properties and good antibacterial effects.
[0006] The method for synthesizing the bionic urethral stent designed by the present invention comprises the following steps: using PVA, borax and carboxymethyl chitosan as main raw materials, preparing a plurality of different solutions, and sequentially adding them into a molding mold to form a multi-layer hydrogel urethral stent; and in the molding process of each layer of the hydrogel urethral stent, the hydrogel urethral stent is formed by freezing and melting once or multiple times.
[0007] A method for synthesizing a bionic urethra stent, characterized in that it comprises the following steps:
[0008] S1: adding a first solution into a first mold cavity, performing one or more freeze-thaw cycles to form a first hydrogel layer to obtain a single-layer hydrogel;
[0009] S2: adding a second solution into the second mold cavity containing the single-layer hydrogel of step S1, and performing one or more freeze-thaw cycles to form a second hydrogel layer on the single-layer hydrogel to obtain a double-layer hydrogel;
[0010] S3: adding a third solution into the third mold cavity containing the double-layer hydrogel of step S2, and performing one or more freeze-thaw cycles to form a third hydrogel layer on the double-layer hydrogel to obtain a three-layer hydrogel;
[0011] S4: Drying the three-layer hydrogel obtained in step S3 to obtain a bionic urethra stent.
[0012] in,
[0013] The first solution, the second solution and the third solution are respectively a PVA solution, a PVA / CMCS solution, and a PVA solution and a borax solution;
[0014] The steps S1-S3 are used to form a PAV / borax hydrogel layer, a PVA hydrogel layer and a PVA / CMCS hydrogel layer respectively, and the three-layer hydrogel obtained in step S3 is a PAV / borax-PVA-PVA / CMCS gel.
[0015] Polyvinyl alcohol (PVA) is a polymer with good biocompatibility and strong polarity. It can easily form a cross-linked structure in solution through intramolecular hydrogen bonds and intermolecular hydrogen bonds. The freeze-thaw process (or freeze-thaw cycle) composed of freezing and thawing can make it cross-linked to form a hydrogel, and its mechanical strength can be effectively adjusted by the number of freeze-thaw cycles and the freeze-thaw time. Using it as the main structure of the urethral stent will be conducive to the development of a bionic stent with the closest mechanical strength to the urethra. At the same time, the complex pathogens in the urine environment can easily cause wound inflammation and are not conducive to repair. The introduction of antibacterial substances such as borax can prevent urethral wound infection caused by bacteria in the urine environment. PVA forms a reversible borate ester bond with borax, which makes the hydrogel have self-healing ability. Combined with its excellent mechanical extensibility, it can play a barrier role like the urethral mucosa, resisting the adverse effects of surgical sutures and urine on wound healing. In addition, carboxymethyl chitosan (CMCS) is an important water-soluble chitosan derivative that has the effects of promoting wound healing, hemostasis, inhibiting scarring, analgesia and antibacterial. After cross-linking of PVA and CMCS, the water absorption is greatly increased and a porous structure is formed, which is conducive to the rapid inoculation of cells and the adhesion and survival of cells in it. Therefore, the construction of a three-layer bionic urethra of PVA / borax-PVA-PVA / CMCS with reference to the native urethral mucosal layer, basal layer and loose connective tissue layer will be more conducive to the repair and reconstruction of the damaged urethra.
[0016] Preferably, the synthesis method of the bionic urethra stent comprises the following steps:
[0017] The first mold cavity, the second mold cavity and the third mold cavity are constituted by the same mold cavity, and each hydrogel layer is formed by adding solutions of different thicknesses therein and performing freeze-thaw treatment, so as to finally obtain a three-layer hydrogel; wherein, after the single-layer hydrogel is formed, the second solution is directly added thereto or it is first demolded and then put back in before adding the second solution, and a second set of freeze-thaw treatment cycles are performed to obtain a double-layer hydrogel, and after the double-layer hydrogel is formed, the third solution is directly added thereto or it is first demolded and then put back in before adding the third solution, and a third set of freeze-thaw treatment cycles are performed to obtain a three-layer hydrogel.
[0018] Preferably, the synthesis method of the bionic urethra stent comprises the following steps:
[0019] The first mold cavity, the second mold cavity and the third mold cavity are composed of different mold cavities, and the depth of the third mold cavity is greater than that of the second mold cavity, and the depth of the second mold cavity is greater than that of the first mold cavity, so that the thickness of the first hydrogel layer is equal to the depth of the first mold cavity, the thickness of the second hydrogel layer is equal to the depth difference between the second mold cavity and the first mold cavity, and the thickness of the third hydrogel layer is equal to the depth difference between the third mold cavity and the third mold cavity; wherein, after the single-layer hydrogel is formed, it is demolded and placed in the second mold cavity to perform a second set of freeze-thaw treatment cycles, and after the double-layer hydrogel is formed, it is demolded and placed in the third mold cavity to perform a third set of freeze-thaw treatment cycles.
[0020] Preferably, in any step S1-S3, a freeze-thaw cycle process is specifically as follows: freezing the mold containing the raw material solution at -10°C to -30°C for a predetermined time, and then leaving it to stand at room temperature to wait for thawing, which can be called a freeze-thaw treatment cycle.
[0021] More preferably, the freezing time is 12-72 hours and the thawing time is 1-12 hours.
[0022] Preferably, freeze drying is adopted in step S4, and the specific conditions of freeze drying of the three-layer urethral stent are: freezing at a temperature of -30°C to -100°C for 3h to 12h, and then vacuum drying for 12h to 36h.
[0023] Preferably, the three-layer urethral scaffold prepared in S4 is inoculated with cells to obtain a three-layer urethral bionic scaffold inoculated with cells on the hydrogel.
[0024] Preferably, the cell inoculation process includes: taking an adipose stem cell suspension into the fourth mold cavity, and laying the three-layer urethral scaffold prepared in S4 on the cell suspension, and immersing the PVA / CMCS surface in contact with the adipose stem cell suspension to perform cell inoculation to obtain a three-layer urethral bionic scaffold inoculated with cells.
[0025] More preferably, the PVA solution and the borax solution are formed by adding PVA or borax into a solvent, and the PVA / CMCS solution is obtained by dissolving CMCS in the PVA solution.
[0026] On the other hand, the present application also provides a bionic urethra stent product, comprising a bionic urethra stent prepared according to any of the methods described above, wherein the bionic urethra stent has a three-layer hydrogel structure and includes a first hydrogel layer, a second hydrogel layer and a third hydrogel layer; the main components of the first hydrogel layer include PVA and borax; the main components of the second hydrogel layer include PVA; the main components of the third hydrogel layer include PVA, CMCS and adipose stem cells.
[0027] Preferably, the PVA forms a reversible borate ester bond with borax.
[0028] Preferably, PVA is cross-linked with CMCS and forms a porous structure.
[0029] The present invention combines three materials with different properties through hydrogen bonds and physical entanglement, so as to give full play to their corresponding advantages and finally make a fully functional bionic urethra. The three-layer bionic urethra has biocompatibility, non-toxicity, degradability and adjustable mechanical strength, and is conducive to cell adhesion and proliferation. It also has self-healing properties and good antibacterial effects, and has achieved initial success in animal experiments. The bionic urethra stent of the present invention has good biocompatibility, non-toxicity, good degradability, adjustable mechanical strength, and is conducive to cell adhesion and proliferation; at the same time, it also has self-healing properties and good antibacterial effects, which solves the problems existing in existing tissue engineering urethra stents: 1. The mechanical strength cannot be adjusted, 2. Poor biocompatibility, 3. Easy to be infected, 4. Poor repair effect and other problems. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the cross-linking of the three-layer structure of the urethral stent of the present invention, wherein the present invention forms a cross-linked structure of the three-layer structure of PVA / borax-PAV-PVA / CMCS by sequentially cross-linking the PVA / borax layer, the PAV layer and the PVA / CMCS layer;
[0031] Figure 2 1 is a schematic diagram showing the three-layer structure of the urethral stent of the present invention;
[0032] Figure 3 This is an electron microscope image of the three-layer structure of the urethral stent of the present invention, in which a relatively obvious three-layer cross-linked structure can be seen;
[0033] Figure 4 It is the water absorption curve of PVA and PVA / CMCS, with the horizontal axis representing time (h) and the vertical axis representing water loss rate (%);
[0034] Figure 5 It is the electron micrograph of PVA / CMCS;
[0035] Figure 6 This is a 3D reconstruction of live and dead cells 3 days after PVA / CMCS was introduced into adipose stem cells;
[0036] Figure 7 This is the self-healing characteristic test diagram of PVA / borax. It can be seen that the two have formed obvious self-healing connection characteristics;
[0037] Figure 8 These are the FTIR curves of PVA, CMCS, Borax, PVA / CMCS, and PVA / Borax;
[0038] Fig. 9 is an XRD diagram, which shows the weakening effect of hydrogen bond strength of PVA after cross-linking;
[0039] Fig.10 This is the tensile test result curve of PVA, PC and PB;
[0040] Fig.11 This is the compression test result curve of PVA, PC and PB;
[0041] Fig.12 It is a peeling test diagram and a schematic diagram of the effect of the bionic stent after peeling;
[0042] Fig.13 This is a general view of the bionic stent of the present invention and the control group after 4 weeks / 8 weeks of use for rabbit urethra repair;
[0043] Fig.14 This is a urethrography image of the bionic stent of the present invention and the control group after being used for rabbit urethra repair for 4 weeks. DETAILED DESCRIPTION
[0044] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0045] raw material
[0046] PVA (polyvinyl alcohol): CAS number is 9002-89-5. This embodiment uses commercially available polyvinyl alcohol;
[0047] Sodium tetraborate: CAS number is 1303-96-4. This embodiment uses commercially available sodium tetraborate decahydrate;
[0048] CMCS (carboxymethyl chitosan): CAS No. 83512-85-0, this embodiment uses commercially available carboxymethyl chitosan;
[0049] Rabbit adipose-derived stem cells: extracted from rabbit inguinal fat, cultured to 80% density and then subcultured, and the third generation of adipose-derived stem cells were prepared into 1×10 6 / ml cell suspension.
[0050] Example
[0051] Example 1
[0052] S1. Configuration of PVA solution:
[0053] Weigh 7g PVA (alcoholysis degree 98%-100%) and add it to 93ml deionized water. Let it stand for 30 minutes to allow the PVA particles to fully expand. Stir and dissolve it in a magnetic stirrer at 90°C and 500r / min for 2 hours until the PVA is completely dissolved to form a uniform particle-free PVA solution. Add deionized water to make the volume 100ml, let it stand and cool for 30 minutes, and then oscillate in ultrasound for 5 minutes to remove tiny bubbles in the solution to prepare a 7wt% PVA solution.
[0054] S2. Preparation of borax solution:
[0055] Weigh 3 g of sodium tetraborate (Na2B4O7·10H2O) and add it to 97 ml of deionized water, stir it thoroughly to dissolve it to form a uniform solution without particles, and prepare a 3 wt% borax solution.
[0056] S3. Configuration of PVA / CMCS solution:
[0057] Weigh 4 g of carboxymethyl chitosan and add it to 100 ml of 7 wt% PVA solution. Stir and dissolve it in a magnetic stirrer at 90°C and 500 r / min for 1 hour until the PVA is completely dissolved. Let it stand and cool for 30 minutes, and ultrasonically vibrate for 5 minutes to remove bubbles in the solution to prepare a PVA / CMCS solution.
[0058] S4. Preparation of three-layer urethral stent:
[0059] Pour the prepared 7wt% PVA solution into the first mold cavity of a concave mold with a length and width of 1×1cm and a depth of 0.4mm. The concave mold can also be called the first mold. Spread it evenly so that the solution plane is flush with the edge of the mold. Be careful to prevent bubbles from forming during this period. Then put it in a -20℃ refrigerator to ensure that the mold is placed on a horizontal surface. Take it out after freezing for 24 hours, let it stand at room temperature for about 2 hours, and put it in a -20℃ refrigerator again after it is fully thawed. After repeated freeze-thaw cycles 3 times in this way, a PVA hydrogel with a certain mechanical strength is formed.
[0060] After the third melting, the PVA hydrogel was gently removed with tweezers to demold, and placed in the second mold cavity of another concave mold with a length and width of 1×1 cm and a depth of 0.8 mm. The concave mold can also be called the second mold. Then pour the prepared PVA / CMCS solution on the surface of the PVA hydrogel and spread it evenly so that the solution plane is flush with the edge of the mold. Put it in a -20℃ refrigerator again to freeze. After repeated freeze-thaw cycles for 3 times, the PVA-PVA / CMCS double-layer hydrogel was obtained.
[0061] The double-layer hydrogel was gently taken out with tweezers for demolding, and then the hydrogel was inverted (PVA side facing up) and placed in the third mold cavity of another concave mold with a length and width of 1×1 cm and a depth of 1.2 mm. The concave mold can also be called the third mold. The PVA solution was evenly spread on the PVA surface of the double-layer hydrogel, and then the borax solution was added and mixed thoroughly. It was gently taken out of the mold with tweezers for demolding, thereby obtaining the PVA / borax-PVA-PVA / CMCS three-layer hydrogel.
[0062] The prepared three-layer urethral stent was frozen in a freeze dryer at -80°C for 6 hours, and then the vacuum drying mode was turned on for 24 hours to prepare a freeze-dried three-layer urethral stent.
[0063] S5. Preparation of urethral bionic scaffold
[0064] 1×10 of the third generation adipose-derived stem cells 6 / ml cell suspension, poured into the fourth mold cavity of another concave mold with a length and width of 1×1cm and a depth of 0.4mm, the concave mold can also be called the fourth mold, and fully and evenly spread. Clamp the freeze-dried three-layer urethral scaffold with tweezers, soak the PVA-CMCS surface in the cell suspension, wait for it to fully absorb the cell suspension for 30 minutes, and obtain a three-layer urethral bionic scaffold with cells seeded on the bottom layer, which can be used to achieve the best repair effect.
[0065] The schematic diagram of the structure of the three-layer urethra bionic stent made in this embodiment is as follows Figure 1 As shown in the figure, the PVA / borax-PVA-PVA / CMCS three-layer bionic urethra is constructed with reference to the native urethral mucosal layer, basal layer and loose connective tissue layer; see the actual picture Figure 2 , the electron microscopic image of the three-layer structure of the urethral stent is shown in Figure 3 , and infrared characterization, microscopic characterization or property characterization of each layer (including PVA, CMCS, Brrax, PVA / CMCS and PVA / Borax), see Figure 4-11 In addition, press Fig.12 The peel test shown in the figure shows that the peel strength between PVA and PVA / CMCS layer is 40.8N / m, and the separation force between PVA and PVA / borax is greater than the tensile force of PVA / borax itself.
[0066] Among them, PVA forms a reversible borate ester bond with borax, which makes the hydrogel self-healing. Combined with its excellent mechanical extensibility, it can play a barrier role like the urethral mucosa, resisting the adverse effects of surgical sutures and urine on wound healing. Carboxymethyl chitosan (CMCS) is an important water-soluble chitosan derivative that has the effects of promoting wound healing, hemostasis, scar inhibition, analgesia and antibacterial. After cross-linking PVA and CMCS, the water absorption is greatly increased and a porous structure is formed, which is conducive to the rapid inoculation of cells and the adhesion and survival of cells in it.
[0067] Comparison Example
[0068] Referring to the steps and contents of Example 1, single-layer PVA scaffolds were prepared as scaffolds for the control group and applied to rabbit urethra repair.
[0069] The repair effect is compared with that of Example 1. Fig.13 , 14 As shown, it can be seen that the bionic stent of the present invention can achieve a good effect of repairing without obvious scars. No obvious scars are seen in naked eye observation and angiography images, and the repair effect is good.
Claims
1. A method for synthesizing a bionic urethral stent, characterized in that: The following steps are involved: S1: adding a first solution into a first mold cavity, performing one or more freeze-thaw cycles to form a first hydrogel layer to obtain a single-layer hydrogel; S2: adding a second solution into the second mold cavity containing the single-layer hydrogel of step S1, and performing one or more freeze-thaw cycles to form a second hydrogel layer on the single-layer hydrogel to obtain a double-layer hydrogel; S3: adding a third solution into the third mold cavity containing the double-layer hydrogel of step S2, and performing one or more freeze-thaw cycles to form a third hydrogel layer on the double-layer hydrogel to obtain a three-layer hydrogel; S4: drying the three-layer hydrogel obtained in step S3 to obtain a bionic urethra stent; in, The first solution, the second solution and the third solution are respectively a PVA solution, a PVA / CMCS solution, and a PVA solution and a borax solution; The steps S1-S3 are used to form a PAV / borax hydrogel layer, a PVA hydrogel layer and a PVA / CMCS hydrogel layer respectively, and the three-layer hydrogel obtained in step S3 is a PAV / borax-PVA-PVA / CMCS gel.
2. The method for synthesizing a bionic urethra stent according to claim 1, characterized in that: The first cavity, the second cavity and the third cavity are formed in the same cavity, and each hydrogel layer is formed by adding solutions of different thicknesses therein and performing freeze-thaw treatment, so as to finally obtain a three-layer hydrogel; wherein, after the single-layer hydrogel is formed, the second solution is directly added thereto or it is first demolded and then put back in before adding the second solution, and a second set of freeze-thaw treatment cycles are performed to obtain a double-layer hydrogel, and after the double-layer hydrogel is formed, the third solution is directly added thereto or it is first demolded and then put back in before adding the third solution, and a third set of freeze-thaw treatment cycles are performed to obtain a three-layer hydrogel; Or, the first mold cavity, the second mold cavity and the third mold cavity are composed of different mold cavities, and the depth of the third mold cavity is greater than that of the second mold cavity, and the depth of the second mold cavity is greater than that of the first mold cavity, so that the thickness of the first hydrogel layer is equal to the depth of the first mold cavity, the thickness of the second hydrogel layer is equal to the depth difference between the second mold cavity and the first mold cavity, and the thickness of the third hydrogel layer is equal to the depth difference between the third mold cavity and the third mold cavity; wherein, after the single-layer hydrogel is formed, it is demolded and placed in the second mold cavity to perform a second set of freeze-thaw treatment cycles, and after the double-layer hydrogel is formed, it is demolded and placed in the third mold cavity to perform a third set of freeze-thaw treatment cycles.
3. The method for synthesizing a bionic urethra stent according to claim 1 or 2, characterized in that: In any step S1-S3, one freeze-thaw cycle is: freezing at -10°C to -30°C for a set time and then standing at room temperature to wait for thawing, which is counted as one freeze-thaw cycle.
4. The method for synthesizing the bionic urethra stent according to claim 3, characterized in that: The freezing time is 12-72h and the thawing time is 1-12h.
5. The method for synthesizing a bionic urethra stent according to claim 1 or 2, characterized in that: In step S4, freeze drying is adopted under the following conditions: freezing at a temperature of -30°C to -100°C for 3h to 12h, and then vacuum drying for 12h to 36h.
6. The method for synthesizing a bionic urethra stent according to claim 1 or 2, characterized in that: The following steps are also included: S5: inoculating cells on the three-layer urethra scaffold obtained by drying in step S4 to obtain a three-layer urethra bionic scaffold inoculated with cells on the hydrogel.
7. The method for synthesizing a bionic urethra stent according to claim 6, characterized in that: Cell inoculation includes: taking adipose stem cell suspension and placing it in the fourth mold cavity, laying the three-layer urethra scaffold obtained in S4 on the cell suspension and immersing the PVA / CMCS surface in contact with the adipose stem cell suspension to perform cell inoculation to obtain a three-layer urethra bionic scaffold inoculated with cells.
8. The method for synthesizing a bionic urethra stent according to claim 1 or 2, characterized in that: The PVA solution and the borax solution are formed by adding PVA or borax into a solvent, and the PVA / CMCS solution is obtained by dissolving CMCS in the PVA solution.
9. A bionic urethra stent product, characterized in that: The bionic urethra stent comprises a bionic urethra stent prepared by the method according to any one of claims 1 to 8, wherein the bionic urethra stent has a three-layer hydrogel structure and comprises a first hydrogel layer, a second hydrogel layer and a third hydrogel layer; the first hydrogel layer contains PVA and borax; the second hydrogel layer contains PVA; the third hydrogel layer contains PVA, CMCS and adipose stem cells.
10. The bionic urethra stent product according to claim 9, characterized in that: The PVA forms a reversible borate ester bond with the borax, and the PVA and the CMCS are cross-linked to form a porous structure.